Are we regressing to more primal behaviours? - Ingle, Kanchan D. (International Journal Of Community Medicine And Public Health, 2024)
The trajectory of human evolution from our primate ancestors has been established through significant modifications in cognitive ability, social systems, and tool use. In recent years, the introduction of mobile technology has added an entirely novel aspect to this evolutionary path, drastically affecting human behaviour, communication, and cognitive processes. This article addresses the potential evolutionary consequences of mobile technology, specifically whether our reliance on these devices represents a return to more primal behaviours or the next phase of our adaptive evolution.